The effect of barley infected with xylanase‐producing filamentous fungi on premature yeast flocculation. Issue 4 (9th September 2022) - Xie, Ying; Cai, Guolin; Xu, Minwei; Han, Bingxin; Li, Cun; Lu, Jian
Abstract : Premature yeast flocculation (PYF) is a sporadic problem in brewery fermentations that results in the incomplete utilisation of fermentable sugars. This work tests the hypothesis that barley or malt infected by xylanase‐producing filamentous fungi contributes to premature yeast flocculation. Ten different fungi and yeasts were isolated and identified from malt and barley husk. These were inoculated onto barley husk and xylanase activity, arabinoxylan and the PYF value determined. The results from the fungal strains ‐ Aureobasidium pullulans, Aspergillus flavus, Fusarium graminearum, and Alternaria tenuissima – indicated involvement in PYF. Small‐scale malting and brewing was used to evaluate the PYF activity of fungal infected barley. The results showed that xylanase activity and arabinoxylan content were significantly ( p < 0.05) related to PYF activity. With the exception of F. graminearum, xylanase activity was detected in the three other fungal isolates. The xylanases reduced the minimum concentration of arabinoxylan required for the induction of PYF. A small‐scale brewing assay showed that xylanase secreted by the four filamentous fungi played a role in PYF. This research will contribute to the development of effective control strategies to prevent PYF factors in malt. © 2022 The Institute of Brewing & Distilling.